Plato's republic. - Ewing, David (Bethesda : Discovery Communications, 1996)
The Republic is a work of art that intrigued, provoked, appalled and inspired readers since it was written in ancient Athens 2500 years ago. Its author, Plato, simultaneously been called the father of philosophy, the first fascist, a revolutionary, and original idealist. To a great extent, the questions and problems first posed by Plato in this book of ideas are the same conflicts men and women are still grabbling with today. In this episode of the Great Books series. Plato's Republic is brought to life in a series of original scenes portraying the citizens of his brave new world.